2009
DOI: 10.1038/nm.2048
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-δ senses and orchestrates clearance of apoptotic cells to promote tolerance

Abstract: Macrophages rapidly engulf apoptotic cells to limit the release of noxious cellular contents and to restrict autoimmune responses against self antigens. Although factors participating in recognition and engulfment of apoptotic cells have been identified, the transcriptional basis for the sensing and silently disposing of apoptotic cells is unknown. Here we show that peroxisome proliferator activated receptor-δ (PPAR-δ) is induced when macrophages engulf apoptotic cells and functions as a transcriptional sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
338
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(351 citation statements)
references
References 47 publications
7
338
2
2
Order By: Relevance
“…Although WT mice are able to cope with this situation, alterations in the noninflammatory clearance of ACs, such as the deletion of Tim4 (40) or absence of Nr4a1, eventually result in the break of self-tolerance to AC-derived Ags. Also, other NRs, such as peroxisome proliferator-activated receptors and liver X receptors, were shown to act as transcriptional sensors for dying cells and to subsequently orchestrate their noninflammatory clearance (41,42). Together with our current data, these findings highlight a key role for NRs as sensors of cell death and coordinators of tissue homeostasis that maintain immune tolerance to "dying self."…”
Section: Discussionsupporting
confidence: 69%
“…Although WT mice are able to cope with this situation, alterations in the noninflammatory clearance of ACs, such as the deletion of Tim4 (40) or absence of Nr4a1, eventually result in the break of self-tolerance to AC-derived Ags. Also, other NRs, such as peroxisome proliferator-activated receptors and liver X receptors, were shown to act as transcriptional sensors for dying cells and to subsequently orchestrate their noninflammatory clearance (41,42). Together with our current data, these findings highlight a key role for NRs as sensors of cell death and coordinators of tissue homeostasis that maintain immune tolerance to "dying self."…”
Section: Discussionsupporting
confidence: 69%
“…Although numerous molecules responsible for recognition and uptake of apoptotic cells and their released nuclear antigen and other debris have been identified, carefully regulating the clearance of apoptotic cells and self nuclear Protein & Cell antigens by macrophages is essential for prevention of autoimmune response in SLE disease (Mukundan et al, 2009). Our previous study revealed that apopDNA obtained from activated syngeneic lymphocyte-derived apoptotic cells could induce macrophage activation , while the present study shows that CRP functions as a regulatory factor to modulate the phagocytic response and prohibit macrophage activation when macrophages are confronted with apopDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Female immune responses are tilted to Th1 with the dominance of IFN-γ, whereas male responses are pushed to Th17, dominated by IL-17 and IL-23. Dunn showed that this was true across species from mice to humans (97,98). Because PPAR-α is targeted by widely used drugs such as gemfibrozil, this dimorphism provides clues that can be translated to therapy with widely used approved drugs for other indications.…”
Section: Translational Research At Stanford Over the Past 20 Yearsmentioning
confidence: 99%
“…Shannon Dunn tackled this problem while a postdoc and has continued her brilliant work in a faculty position at the University of Toronto. We published a series of reports in the Journal of Experimental Medicine and Nature Medicine (96)(97)(98) describing the role of peroxisome proliferator-activated receptor (PPAR)-α and PPAR-δ in regulating the sexual dimorphism. PPAR-α is overexpressed on male T cells.…”
Section: Translational Research At Stanford Over the Past 20 Yearsmentioning
confidence: 99%